Нелинейная многомерная теория релятивистского генератора дифракционного излучения - Одаренко, Е. Н.; Шматько, А. А. (Издательство "Радиотехника", 2007)
The multidimensional nonlinear non-stationary equations self-consistent set of the O-type relativistic resonance generator is obtained. The equations set allows to investigate the beam-wave interaction and to obtain output characteristics of the generator at the arbitrary focusing magnetic field space configuration and arbitrary amplitude distribution of the high-frequency oscillatory system field. The operating characteristics of the diffraction radiation relativistic generator at an initial stage of generation and in steady-state mode such as starting current, efficiency, frequency pushing are researched. The effect of the magnetic focusing field, local magnetic discontinuity and relativistic mass-factor on these characteristics has been considered. The analysis of nonlinear modes of the steady-state oscillations for a case of weak and strong magnetic focusing fields is carried out.
Keywords: генератор дифракционного излучения; нелинейная теория; релятивистский прибор; многомерная модель